Exploratory Study on the Relationship between Good Public Governance and National Competitiveness - HANDOYO, SOFIK (Universitas Muhammadiyah Yogyakarta, 2017)
This study aims to examine empirically the relationship between good public governance and national competitiveness. The motivation behind the study was the desire to answer a cosmic question regarding the association between the implementation of good public governance and the capability of a country to compete in the global market. An exploratory research design was applied in this study. Public governance and national competitiveness were treated as two in- dependent variables. Public governance was broken down into attributes, namely public accountability, government effectiveness, the quality of government regulation, government control toward corruption, the rule of law and a country’s political stability. The World Governance Index (WGI) was used to measure public governance. Meanwhile, the Global Competitiveness Index (GCI) was adopted to measure national competitiveness. Bivariate correlation analysis was applied in this study and involved 140 countries that are officially listed as World Bank members. The findings concluded that public governance had a positive association with national competitiveness. All attributes of public governance showed a positive and significant correlation with national competitiveness. Statistical analysis using Pearson correlation indicated that all public governance attributes indicated a solid correlation (r 0.6, p 0.01) except for political stability (r = 0.585, p 0.01) and public accountability (r= 0.541, p 0.01). Although the results revealed that not all public governance attributes had a strong correlation with national competitiveness, the nature of the correlation has already been justified. The results imply that if the government implements good public governance practice, it might have a positive impact on the capability of the nation to create power to compete with other countries in the global market .